Wellness Programs and Engagement of Information Technology Workforce - John Britto, M; Magesh, R (International Journal of Engineering and Technology, 2018)
Physical, mental and spiritual well-being is the secret to success but employees in their quest for glory and money fail to maintain a balance between the three. Their workplace is the most affected when wellness of employees is at stake which would eventually decide the culture and fate of organisations in a dynamic global village. The current research analyses the effect of wellness programs at the workplace on employee engagement.Â Â